The impact of visual stimulation of product packaging on the gustatory aspects of consumers: a study on synesthetic cross modal correspondence in the sri lankan context - Thavendrakumar, V. (University of Jaffna, 2022)
Purpose: The present study is aimed at exploring the impact of visual stimulation of product packaging on the gustatory aspects of consumers. This is based on synesthetic cross-modal correspondence. This study evaluates the research problem of whether visual stimulation (colour) of the product packaging, influence the taste of the product. Methodology: The research carried out an experiment to test the hypotheses developed in line with the objectives of the study. This is an empirical research conducted in Sri Lankan context. In the present study there were two dependent variables. The first variable is the taste perception of product packaging color and the second variable is the perceived taste intensity of package color. Only two sub variables such as sweetness and sourness were considered. The variables were measured using a seven-point Likert scale by asking the respondents to give ratings based on their perceptions. The hypotheses were tested using one-way ANOVA method. Findings: The Findings of the present study showed a non-existence of cross-modal correspondence between color of the packaging and taste. However, when only the mean values are considered, they showed certain associations between the wrapper color and the taste perception. In this study, even though the candy is wrapped in four different colors, the candy itself is white in color. It might have influenced the taste perceptions of the subjects. However, expectations produced by the packaging can be rejected if information from that source does not agree with the sensory experience of the product. Research limitations: Major limitation of this study was the number of respondents in each experiment group. A large group of sample would have improved the validity and accuracy of the experiment and the results. This research only considered about the cross-modal correspondence between colour of the product packaging and taste aspects. Implications: The Findings of this study would be useful to the product developers, designers and marketers to realize the importance of the role of packaging and how the color of the packaging plays a critical role in determining the taste of the products. Based on the outcomes, it can be drawn that the marketers don't need to spend much time and effort in deciding on the colours of the package since it doesn't have any significant influence. However, taking the past research and studies into consideration, the connection between the packaging colours and the taste aspects cannot be ignored or underestimated.
Keywords: Multi-sensory marketing; Packaging; Cross-modal correspondence